Manajemen Kreativitas Pengajaran Musik Pendidikan Anak Usia Dini di Masa Pandemi Covid 19 - Christina Dwi Hartanti; Hari Sasongko (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2021)
The education of early childrenÂ  before entering primary school level is significant for child development. The government views this as important with the issuance of the National Education System Law No. 20/2003, Article 28, Paragraph 1 concerning PAUD (Early Chilhood Education), which focuses on laying the foundation toward growthÂ  and six developmentÂ  namely religion dan morals, physical/motoric, cognitive, language, socio-emotional and art. Based on Permendikbud (education system law from ministry department of education and culture) No. 137 of 2014, the goals of PAUD are stated; namely the main goal (quality children) and the objective of the companion (helping readiness to learn). One of the fields that must be developed to support the above goals is music. From various studies concluded, music is a field that greatly affects the development of children at an early age. One the other hand, the success of the goal cannot be separated from the role of the teacher who interacts with students on a daily basis, the teacher-student â€œmeetingâ€ or â€œinteractingâ€ is very important, bacause from the meeting the transformation of knowledge contained in the National Education System Law and Permendukbud can be achieved; the presence of teachers is very important in realizing educational goals. However, with the Covid-19 pandemic, the above methods inevitably have to change; there are no more physical encounters, and the learning process through sosial media has changed the method of teaching music. This is where a teacher is challanged to be more creative so that the learning process continous to run effectively and still refers to the emphasis and goals of PAUD education itself.Keywords: PAUD, creativity, music, transformation of knowledge.Â AbstrakPendidikan anak-anak sebelum memasuki tingkat sekolah dasar cukup signifikan bagi pengembangan anak. Pemerintah memandang penting hal itu dengan dikeluarkannya UU Sisdiknas No. 20/2003, Pasal 28, Ayat 1 tentangÂ  PAUD (Pendidikan Anak Usia Dini), yang menitikberatkan pada peletakan dasar ke arah pertumbuhan dan enam perkembangan, yakni agama dan moral, fisik/motorik, kognitif, bahasa, sosial-emosional dan seni. Berdasarkan Permendikbud 137 tahun 2014 disebutkan tujuan PAUD, yakni tujuan utamaÂ  (anak yang berkualitas) dan tujuan penyerta (membantu kesiapan belajar). Salah satu bidang yang harus dikembangkan untuk mendukung tujuan di atas adalah bidang musik. Dari berbagai penelitian disimpulkan, musik adalah bidang yang sangat mempengaruhi perkembangan anak di usia dini. Di sisi lain keberhasilan tujuan ini tidak dapat dilepaskan dari peran guru yang melakukan interaksi dengan siswa sehari-hari. â€œpertemuanâ€ antara guru-siswa menjadi sangat penting, sebab dari pertemuan itulah transformasi ilmu yang terdapat di dalam UU Sisdiknas dan Permendikbud di atas dapat tercapai; kehadiran guru menjadi sangat penting dalam merealisasikan tujuan pendidikan. Akan tetapi dengan adanya Pandemi Covid 19, metode di atas mau tidak mau harus berubah: tidak ada lagi pertemuan fisik, dan proses pembelajaran melalui sosial media, maka metode pengajaran musik pun berubah. Di sinilah seorang guru ditantang untuk lebih kreatif agarÂ  proses pembelajaran tetap berjalan efektif dan tetap mengacu pada titik berat dan tujuan pendidikan PAUD itu sendiri.Kata kunci: PAUD, kreativitas, musik, transformasi ilmu